THE PARADOX OF THE NIGERIAN STATE, POLICING AND THE OVERACHING CHALLENGES OF BANDITRY (CAHIERS MAGELLANES-NS, 2024)
This study analyses the context in which the Nigerian citizen inheres with the objective to investigate the essence of the state in Nigeria which ought to bend towards providing the security template for the good life of an average Nigerian hence the capacity of the state to guarantee adequate security has become a primary index to assessing the failure or success of the state. However, the state in Nigeria rather that fulfilling this public good seem liable for the deteriorating conditions that consequently impede on the state of security in the country, especially with respect to terrorism, the menace of banditry and kidnapping for ransom across the country. Thus the specific objectives of the study are: identify the various causes and trggers of banditry in Nigeria; account for the manifestations and dimensions of bandiry in Nigeria, and; identify its implications and possible solutions. The research design emplyed by the authors is the qualitative research approach, while we interrogated the state of insecurity in the country from an eclectic lens resting on theoretical axiom that burrows into good governance as basis for the pursuit for peace (pax mundi), the failed state index and the frustration-aggression hypothesis. The research findings show that the crisis of banditry is inextricably linked to the overall development aspirations of the country, and thus recommends that the solution to the crisis of insecurity lays in the integrity of the state, deriving from its capacity to reenact itself in its functional institutions and agencies.